THE CONTRIBUTION OF JASSER AUDA IN MAQASHID AL SYARI’AH CONCEPT ON ISLAMIC EDUCATION PSYCHOLOGY - Sangkot Sirait; Erika Setyanti Kusuma Putri; Evita Yuliatul Wahidah; Benny Prasetiya; Ulfa Ulfa (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2022)
The academic problems in this research is to answer the position of Islamic Educational Psychology that should be, by trying to view Islamic Educational Psychology from a philosophical perspective, for more precisely maqashid shari'ah.Maqashid syari'ah which was initiated by Jasser Auda is actually used for legal/sharia studies as a form of contemporary philosophy that responds to the dullness of the two previous philosophies, which are modern and postmodern philosophy. The concept of maqashid shari'ah that is often called the system philosophy approach has contributed to analyze the Islamic Education Psychology. With the six features, which are: Cognitive traits, Wholeness, Openness, Interrelated Hierarchies, Multi-dimensional, Always Aiming (purposefulness), that become the frame of reference in this paper to analyze Islamic Educational Psychology.This research began by reviewing the biography and thoughts of Jasser Auda about maqashid shari'ah, that continued by Jasser Auda's recommendations in system analysis. The next study examines the contribution of Jasser Auda's maqashid al syari'ah in Islamic Educational Psychology which shows that Islamic Educational Psychology is a dynamic discipline.  Keywords: Maqashid Al-Syari’ah, Jasser Auda, Islamic Education Psychology